Effect of cold and warm Juglans nigra L. walnut leaves extract on fat in rats infected with high blood lipid level with hydrogen peroxide and cholesterol - Khalid Hammadi Hameed Sharaf; Jian Salam Hasan Ali (College of Education for Pure Sciences, 2013)
Abstract Forty-five albino adult male rats severed from oxidative stress induced with 0.5% hydrogen peroxide and 1% cholesterol for 45days(30 days for the preparation of oxidative stress and 15days for therapeutic treatment of experimental period),and aged 3-4 months were used as experimental model for oxidative stress study in rats.Rats were dividedrandomly into nine groups. First group was used as control, second to fifth groups were orally treated with walnut leaves coldextract, and the sixth to ninth groups were treated separately with warm extract concentration 60, 75, 90 and 120 mg/kg body weight for the two walnut extracts respectively. Rats were fed with hyperlipidemicdiet, which contains 1% cholesterol and 0.5% hydrogen peroxide in drinking water for 15 days experimental period;at room temperature around 25°C in dark/light cycle was 12/12 hours daily. Blood samples were collected from the eye retro-ocular vein using heparinized PCV tubeat the beginning and last days of experiment. Plasma was separated and used for the determinations of blood total lipid (TL), total cholesterol (TC), high density lipoprotein (HDL-c), and liver total cholesterol. Rat's nutritional status (increased body mass-growth and food intake weights) was estimated too. Analysis of variance and Duncan test showed that, the cold and warm extracts of walnut leaves caused rat's nutritional status improvement and hypolipidemic effect in plasma TL, TC, VLDL-c &LDL-c and decreased atherogenicindices;in addition they increased the HDL-c and lowering liver total cholesterol. The walnut leaves cold extract concentration 75mg/kg body weight considered to be more efficient than other tested concentrations of cold and warm extracts. Therefore, this concentration of cold walnut extract was suggested as hypolipidemic matter with specific concentration.